1996
DOI: 10.1021/ma9608840
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Controlled/“Living” Radical Polymerization of Styrene in the Presence of Nitroxyl Radicals. Kinetics and Simulations

Abstract: The polymerization of styrene in the presence of a stable radical, TEMPO (2,2,6,6-tetramethyl-1-piperidinyloxy), has been simulated using a Predici simulations package. On the basis of the experimental data, a kinetic model for the TEMPO-mediated polymerization of styrene is proposed. In order to simulate the experimental data properly, it was necessary to include thermal self-initiation, transfer, and irreversible decomposition of intermediate alkoxyamines in addition to the reversible cleavage of the TEMPO-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
294
1
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 268 publications
(310 citation statements)
references
References 58 publications
14
294
1
1
Order By: Relevance
“…According to Matyjaszewski et al 27) and Fukuda et al 28) thermal initiation is essential for the TEMPO-system. Although vinylferrocene polymerizes thermally, the homopolymerization of vinylferrocene did not show the features of a controlled radical polymerization.…”
Section: Results and Discussion (A) Random Copolymers P(s/vfc) And Pmentioning
confidence: 99%
“…According to Matyjaszewski et al 27) and Fukuda et al 28) thermal initiation is essential for the TEMPO-system. Although vinylferrocene polymerizes thermally, the homopolymerization of vinylferrocene did not show the features of a controlled radical polymerization.…”
Section: Results and Discussion (A) Random Copolymers P(s/vfc) And Pmentioning
confidence: 99%
“…The basic kinetic scheme of the second studied RDRP, i.e., NMP [17,35], is shown in Figure 1 (right panel). NMP is one of the first discovered RDRP systems, due to the pioneering work of Rizzardo et al [36].…”
Section: Introductionmentioning
confidence: 99%
“…At higher conversions, the plots tend to plateau. The reason for the plateau could be attributed to the chain transfer side reactions to the solvent and monomers, which become more prevalent at higher conversions [63]. However, it should be noted that the styrenic comonomer tended to be incorporated preferentially into each of the copolymers, and the preferential incorporation could have led to irreversible termination reactions at a higher conversion, as the controlling co-monomer concentration would be steadily depleted or removed completely.…”
Section: Characterization Of Nlam/x Statistical Copolymersmentioning
confidence: 99%
“…The newly created chains are probably still able to polymerize in a controlled manner, but with a significant fraction of new chains at low molecular weight, this would result in a lower than expected � and a broader molecular weight distribution. Greszta et al demonstrated that the combination of chain transfer to monomer and alkoxyamine decomposition were the main reasons for lower � and higher � � ⁄ at high conversions in the polymerization of styrene with TEMPO nitroxide [63].…”
Section: Characterization Of Nlam/x Statistical Copolymersmentioning
confidence: 99%